2017
DOI: 10.1371/journal.pone.0179076
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of stayability in Nellore cattle

Abstract: Stayability, which can be defined as the probability of a cow calving at a certain age when given the opportunity, is an important reproductive trait in beef cattle because it is directly related to herd profitability. The objective of this study was to estimate genetic parameters and to identify possible genomic regions associated with the phenotypic expression of stayability in Nellore cows. The variance components were estimated by Bayesian inference using a threshold animal model that included the systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
2
7
0
Order By: Relevance
“…who presented heritability estimates of STAY63 in Nellore cattle ranging from 0.03 to 0.07. In contrast, the results of the present study corroborate withTeixeira et al (2017) andBonamy et al (2018) who reported heritability for STAY63 of 0.14 and 0.16, respectively. Prediction accuracy (r) of estimated breeding values (EBVs), genomic EBVs (GEBVs) and bias obtained through the BLUP and ssGBLUP methods for four stayability traits, and the percentage of increase in prediction accuracy (>Acc) obtained by the ssGBLUP method, in Nellore cattle…”
supporting
confidence: 91%
“…who presented heritability estimates of STAY63 in Nellore cattle ranging from 0.03 to 0.07. In contrast, the results of the present study corroborate withTeixeira et al (2017) andBonamy et al (2018) who reported heritability for STAY63 of 0.14 and 0.16, respectively. Prediction accuracy (r) of estimated breeding values (EBVs), genomic EBVs (GEBVs) and bias obtained through the BLUP and ssGBLUP methods for four stayability traits, and the percentage of increase in prediction accuracy (>Acc) obtained by the ssGBLUP method, in Nellore cattle…”
supporting
confidence: 91%
“…Positive values observed for CC top 5%, CC top 10%, and RC 100% indicate agreement between the models to select the best animals. These results may be due to the advantage of using H −1 matrix intead of A −1 when, for example, the farms adopt the multiple-sire mating system, which is common in Brazil (Teixeira et al, 2017). In such a situation, the relationship matrix based on pedigree is much less informative than the genomic relationship matrix due to the occurrence of many offspring with unknown paternity.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, one drawback of ssGWAS approaches is the inability to determine SNP significance levels (Wang et al, 2012). Despite that, various important genomic regions have been unraveled by using this method in a variety of traits in cattle (Barreto Amaral Teixeira et al, 2017;Medeiros de Oliveira Silva et al, 2017;Melo et al, 2017), aquaculture (Vallejo et al, 2017), and pigs (Wu et al, 2018).…”
Section: Gwas and Functional Analysesmentioning
confidence: 99%